2014
DOI: 10.1038/bjc.2014.228
|View full text |Cite
|
Sign up to set email alerts
|

Tropomyosin-related receptor kinase B at the invasive front and tumour cell dedifferentiation in gastric cancer

Abstract: Background:Tropomyosin-related receptor kinase B (TrkB) promotes proliferation and invasion, relating to poor prognosis of various malignancies. We examined the role of TrkB at the invasive front of gastric cancer (GC) and its association with tumour cell dedifferentiation and tumour budding.Methods:Immunoreactive TrkB was evaluated at the tumour centre and margin using whole-tissue sections of 320 GC patients. Tumour cell dedifferentiation was defined as higher histologic grade at the tumour margin than the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 28 publications
1
52
0
Order By: Relevance
“…However, on multivariate analysis higher tumor bud scores were also associated with recurrence (hazard ratio 1.60), but the P-value approached, but did not meet significance (P=0.08). Our results agree with previous research [18,25,26], supporting the hypothesis that increased tumor budding in GAC portends an increased risk of adverse outcomes, including lymph node involvement and recurrence. However, more studies are needed to better analyze the value of tumor budding in gastric carcinoma.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
See 2 more Smart Citations
“…However, on multivariate analysis higher tumor bud scores were also associated with recurrence (hazard ratio 1.60), but the P-value approached, but did not meet significance (P=0.08). Our results agree with previous research [18,25,26], supporting the hypothesis that increased tumor budding in GAC portends an increased risk of adverse outcomes, including lymph node involvement and recurrence. However, more studies are needed to better analyze the value of tumor budding in gastric carcinoma.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…Tanaka et al also found that a high level of tumor budding was associated with increasing T-stage, N-stage, lymphatic involvement, and metastasis on univariate analysis, but did not maintain significance in multivariate analysis combined with TNM staging [25]. Of note, similar to our methodology, both of these investigators excluded the signet ring and undifferentiated tumors from their analysis.…”
Section: Accepted Manuscriptmentioning
confidence: 52%
See 1 more Smart Citation
“…In addition, various critical molecular events that regulate tumour proliferation, adhesion/migration, and angiogenesis occur in the ITF (Bankfalvi and Piffko, 2000; Rowe and Weiss, 2009; Sharma et al , 2013). Accordingly, the ITF is mainly responsible for the clinical behaviour of the tumour (Khanh do et al , 2011; Tanaka et al , 2014). However, it is not clear whether the presence of CSCs at the ITF has clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Yet in recent studies, increasing evidence has revealed that both BDNF and its receptor TrkB are overexpressed in a variety of malignances, including head and neck squamous cell carcinoma (21), breast cancer (6), colorectal cancer (7), hepatocellular cancer (22) and gastric cancer (23). Overexpression of these two markers in malignant tumors is consistently associated with a more aggressive behavior and poor prognosis (6,7,(21)(22)(23). Furthermore, our previous studies demonstrated that overexpression of BDNF/TrkB is significantly correlated with clinical stage, perineural or vascular invasion, distant metastasis, and poor prognosis of SACC (8).…”
Section: Discussionmentioning
confidence: 99%